Um estudo didático sobre a tomada de decisões financeiras no Ensino Médio - Martins, Fabiana Venhoven (2023)
This research presents a didactic study on Financial Education, guided by the question: “what knowledge, mathematical or not, are mobilized by high school students to take critical and complex financial decisions, facing situations contextualized in the Brazilian reality?”. In order to answer this question, the conceptual framework of Didactic Engineering were used and, supported by the Theory of Didactic Situations, a learning sequence consisting of five situations related to investments and indebtedness common to Brazilians was developed. From the analysis of the data collected in the application of the learning sequence, it can be concluded that the contextualization of situations in the current Brazilian economic scenario is a positive factor in promoting greater reflection by the students and providing validating parameters for their conclusions. Negative factors identified were the strong presence of an implicitly established didactic contract, which promotes the mechanization of tasks and uncritical thinking by students, and the inadequacy of textbooks to encourage the development of more critical students